Repenser le risque et les catastrophes dans les régions de montagne - Kenneth Hewitt; Manjari Mehta (Revue de Géographie Alpine)
This chapter presents a view of risk and disaster in the mountains that finds them fully a part of public safety issues in modern states and developments, rather than separated from them. This contrasts with prevailing approaches to disaster focused on natural hazards, “unscheduled” or extreme events, and emergency preparedness; approaches strongly reinforced by mountain stereotypes. Rather, we find the legacies of social and economic histories, especially relations to down-country or metropolitan actors, are decisive in shaping contemporary “mountain realities”. Developments in transportation, resource extraction and tourism that serve state and international agendas can increase rather than reduce risks for mountain populations, and undermine pre-existing strategies to minimise environmental dangers. Above all, we see rapid urbanisation in mountains generally and the Himalaya in particular as highly implicated in exacerbating risks and creating new types of vulnerabilities. Enforced displacement, and concentration of, people in urban agglomerations, is a major part of the modern history of mountain lands that invites more careful exploration. Rapid expansion of built environments and infrastructure, without due regard to hazards and structural safety, introduce new and complex risks, while altering older equations with and to the land and sapping people’s resilience. In the lives of mountain people, environmental hazards are mostly subordinate to other, societal sources of risk and vulnerability, and to the insecurities these involve. Basically we conclude that “marginalisation” of mountain lands is primarily an outcome of socio-economic developments in which their condition is subordinated to strategic planning by state, metropolitan and global actors.